Clinical presentation, complications, and outcomes of hospitalized COVID‐19 patients in an academic center with a centralized palliative care consult service. Issue 4 (2nd November 2021) - Baker, Sarah M.; Leedy, Doug J.; Klafter, Jesse Abbott; Zhang, Yilin; Secrest, Kayla M.; Osborn, Tristan R.; Cheng, Richard K.; Judson, Seth D.; Merel, Susan E.; Mikacenic, Carmen; Bhatraju, Pavan K.; Liles, W. Conrad
Abstract: Background and Aims: Palliative care is a critical component of the response of a healthcare system to a pandemic. We present risk factors associated with mortality and highlight an operational palliative care consult service in facilitating early identification of risk factors to guide goal‐concordant care and rational utilization of finite healthcare resources during a pandemic. Methods: In this case series of 100 consecutive patients hospitalized with COVID‐19, we analyzed clinical data, treatment including palliative care, and outcomes in patients with SARS‐CoV‐2 infection admitted to three hospitals in Seattle, Washington. We compared data between patients who were discharged and non‐survivors. Results: Age (OR 4.67 [1.43, 15.32] ages 65‐79; OR 3.96 [1.05, 14.89] ages 80‐97), dementia (OR 5.62 [1.60, 19.74]), and transfer from a congregate living facility (OR 5.40 [2.07, 14.07]), as well hypoxemia and tachypnea (OR 7.00 [2.91, 22.41]; OR 2.78 [1.11, 6.97]) were associated with mortality. Forty‐one (41%) patients required intensive care and 22 (22%) invasive mechanical ventilation. Forty‐six (46%) patients were seen by the palliative care service, resulting in a change of resuscitation status in 54% of admitted patients. Fifty‐eight (58%) patients recovered and were discharged, 34 (34%) died, and eight (8%) remained hospitalized, of which seven ultimately survived and one died. Conclusions: Older age, dementia, and congregate living were associated with mortality. Early discussions of goals of care facilitated by an operational palliative care consult service can effectively guide goal‐concordant care in patients at high risk for mortality during a pandemic. Development of a functional palliative care consult service is an important component of pandemic planning.